2017
DOI: 10.1002/chem.201701867
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Thioethers as Novel Luminophores with Aggregation‐Induced Fluorescence and Phosphorescence

Abstract: Here we report on a novel system based on aromatic thioethers with unique luminescence properties. Fifteen different compounds were investigated in detail on their luminescence properties using UV/Vis absorption and steady-state and time-resolved luminescence spectroscopy. Excited state lifetimes as well as quantum yields were determined, and the toxicity towards HeLa cells was investigated. Besides X-ray analyses also quantum chemical calculations were performed to gain deeper insights in the unique behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 66 publications
2
60
0
Order By: Relevance
“…Recently Voskuhl and co‐workers discovered a novel class of small molecule emitters with aggregation‐induced phosphorescence properties . This system combines, in an elegant fashion, the facile synthesis (one‐step reaction) together with unique photophysical properties.…”
Section: Aggregation‐induced Phosphorescencementioning
confidence: 99%
See 2 more Smart Citations
“…Recently Voskuhl and co‐workers discovered a novel class of small molecule emitters with aggregation‐induced phosphorescence properties . This system combines, in an elegant fashion, the facile synthesis (one‐step reaction) together with unique photophysical properties.…”
Section: Aggregation‐induced Phosphorescencementioning
confidence: 99%
“…Recently Voskuhl and co-workersd iscovered an ovel class of small molecule emittersw ith aggregation-induced phosphorescence properties. [21] This system combines, in an elegant fashion,t he facile synthesis (one-step reaction) together with unique photophysical properties. To this end, aromatic tetrathioethers were synthesised with functional groups such as carboxylic acids or hydroxyl moieties (9-11)( Figure 5).…”
Section: Aggregation-induced Phosphorescencementioning
confidence: 99%
See 1 more Smart Citation
“…[59] While most of these emitters displayed fluorescence, the authors found that two of the examples, 80 and 81 (Figure 15), displayed phosphorescence at 556 nm and 544 nm with lifetimes of 4.95 and 0.87 ms respectively. [59] While most of these emitters displayed fluorescence, the authors found that two of the examples, 80 and 81 (Figure 15), displayed phosphorescence at 556 nm and 544 nm with lifetimes of 4.95 and 0.87 ms respectively.…”
Section: Boron Phosphorus and Sulfurmentioning
confidence: 99%
“…[14][15][16][17] Luminogens with AIE features have been defined as AIEgens by Tang. [3] To date, AIEgensh ave been used in av ariety of fields such as organic light-emitting diodes, [18][19][20][21][22][23] chemosensors [24][25][26][27][28][29][30] and biosensors. [31][32][33][34][35][36] Experimental results and theoretical analysis have consistently revealed that the restriction of intramolecular motions (RIM), which includes the restriction of intramolecularr otations (RIR) and the restriction of intramolecular vibration (RIV), is attributable to the mechanism of the AIE effect.…”
Section: Introductionmentioning
confidence: 99%